Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors

Calculator Output

Simplifying
-7 + x + 4 + 4x = x + -3 + 6 + 3x

Reorder the terms:
-7 + 4 + x + 4x = x + -3 + 6 + 3x

Combine like terms: -7 + 4 = -3
-3 + x + 4x = x + -3 + 6 + 3x

Combine like terms: x + 4x = 5x
-3 + 5x = x + -3 + 6 + 3x

Reorder the terms:
-3 + 5x = -3 + 6 + x + 3x

Combine like terms: -3 + 6 = 3
-3 + 5x = 3 + x + 3x

Combine like terms: x + 3x = 4x
-3 + 5x = 3 + 4x

Solving
-3 + 5x = 3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 5x + -4x = 3 + 4x + -4x

Combine like terms: 5x + -4x = 1x
-3 + 1x = 3 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + 1x = 3 + 0
-3 + 1x = 3

Add '3' to each side of the equation.
-3 + 3 + 1x = 3 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 3 + 3
1x = 3 + 3

Combine like terms: 3 + 3 = 6
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6
Processing time: 1 ms. 51501956 equations since February 08, 2004.   Disclaimer

Equation Calculator & Solver

Equation: Variable:
       
Hint: Selecting "AUTO" in the variable box will make the calculator automatically solve for the first variable it sees.

Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors